Twardowski: content as mediator between the act and the object of presentation. - Pires, Jesuino Junior (Cognitio-Estudos: revista eletrônica de filosofia, 2019)
The purpose of this article is to investigate the notion of content of presentation as stated by Kasimir Twardowski in his opuscule Zur Lehre vom Inhalt und Gegenstand der Vorstellungen. In proposing the distinction between act, content and object, Kasimir Twardowski thinks he is making a correction of the Brentanian theory of psychic phenomena that in the face the physics phenomenon always has an immanent object, intentional. Thus, in Franz Brentano’s Psychologie vom Empirischen Standpunkt, considers content and object as synonyms. However, with a new structure of psychic phenomena, which is now divided into three elements by Twardowski (act, content and object), doubts arise regarding the status of the content. This is due to the way the Polish philosopher presents and assimilates his notion of content to Höfler’s notion, where content functions as a mere psychic “copy” (Abbild), as if it were a mental substitute for the object. There is in Twardowskian thought a positive definition of content rather than a mere distinction between content and object, nor the claim that content functions as a mere psychic image (Bild) of the object. The Polish philosopher thus reformulates the theory of the functions of the name by establishing a parallel between names and presentations, where meaning has the mediating function, such as content. In this respect, we can see points of convergence between Frege’s differentiation between sense and reference and Twardowski’s between content and object. We infer, therefore, that conceiving the content as mediator between the act and the object is one of the peculiarities of the distinction proposed by Twardowski in Zur Lehre.